Analysis of Teacher Needs for the Development of Ethno-ESD-Based Science Modules in Elementary Schools - Hesti Widia Astuti; Ghullam Hamdu (Postgraduate, University of Mataram, 2026)
Science learning in elementary schools is frequently dominated by traditional, teacher-centered instruction that fails to systematically cultivate students' 21st-century competencies, particularly critical thinking skills. While ethnoscience and Education for Sustainable Development (ESD) offer powerful contextual frameworks, previous research often addresses them in isolation, leaving a critical gap in integrated instructional designs that are rooted in empirical field needs. This study aims to analyze teacher needs regarding the development of an integrated Ethno-ESD science module to strategically strengthen critical thinking in primary education. Operating within the initial analysis phase of a design-based research (DBR) framework, this study employed a descriptive qualitative approach. Data were collected through semi-structured interviews with two grade IV public elementary school teachers selected via purposive sampling. The thematic analysis revealed distinct categories of structural needs: (1) a shift from rote-memorization tasks toward structured problem-based inquiry, (2) the systematic integration of local cultural contexts—specifically traditional palm sugar production—as core learning frameworks rather than incidental examples, and (3) the inclusion of explicit critical thinking rubrics and argumentation tasks. These findings provide an empirical foundation and design specifications for developing actionable Ethno-ESD learning modules in the subsequent phase of research.